Antibiogram Profile of Patients Having Urinary Tract Infection Treated with Most Commonly Used Antibiotics - Bilal Ahmad; Faleesha Gul; Said Hassan; Haseeba Arif; Amber Javaid; Shawkat Ali (Pakistan Journal of Medicine and Dentistry)
Background: Urinary tract infections (UTIs) are the most common infections in humans, primarily caused by bacteria, with Escherichia coli (E. coli) responsible for 75-90% of cases. The rise in bacterial resistance is largely due to inappropriate antibiotic use, posing significant public health concerns. This study investigated UTI prevalence and antibiotic resistance to inform optimized treatment guidelines. This study aimed to identify the bacterial pathogens causing UTIs and assess their antimicrobial sensitivity and resistance to commonly used antibiotics.